The Black Dahlia - Ellroy, James 1948-; Matz 1967-; Fincher, David 1962- (Archaia, 2016)
"LAPD investigators Bucky Bleichart and Lee Blanchard find themselves enthralled with the mysterious and brutal murder of a beautiful young woman, Elizabeth Short. Their obsession takes a dark turn as they delve into the underbelly of Hollywood and the heart of the dead woman's tortured and twisted past. It is a case that will test their mettle and their sanity." --
Keywords: Police -- California -- Los Angeles -- Comic books, strips, etc; Young women -- Crimes against -- Comic books, strips, etc; Frauenmord; Kriminalbeamter; Los Angeles (Calif.) -- Comic books, strips, etc; Los Angeles- Hollywood; Short, Elizabeth / 1924-1947 / Comic books, strips, etc; Murder / Investigation / California / Los Angeles / Comic books, strips, etc; Murder; Police; Young women; Noir comics; Comics (Graphic works); Graphic novels; Mystery comic books, strips, etc; Comic; Detective and mystery stories